Narrativa crítico-reflexiva sobre a vivência no curso de medicina em uma universidade federal: jornada de encontro a um propósito de cuidado - Rossi, Camila Félix (Universidade Federal de São Carlos, 2025)
This Final Course Project (TCC) presents a critical-reflective narrative of the author's experience in the medicine course at the Federal University of São Carlos (UFSCar), with the aim of describing her personal and professional journey and her encounter with a purpose of humanised care. This trajectory motivated the proposal of an ongoing research project, based on an integrative review of Child-Centred Care (CCC).
Critical-reflexive narrative about the experience in the medicine course at a federal university: journey towards a purpose of care
Keywords: Medicina; Narrativa reflexiva; Cuidado centrado na criança; Medicine; Reflective narrative; Child-centred care; CIENCIAS DA SAUDE::MEDICINA